Peningkatan Hasil Belajar Pkn Melalui Metode Diskusi Pada Materi Norma dan Aturan Di Kelas V SD Muhammadiyah 2 Kota Cirebon - Ulfa Wahyuni; Nugraha Permana Putra; Prabawati Nurhabibah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by the observations that have been made. There are still many passive students during classroom learning who are not confident in making decisions and issuing opinions during learning. Students do not understand the norms and rules in PKN lessons in the school environment, and students are still not polite in their daily lives, so the researcher intends to conduct research in Class V of SD Muhammadiyah 2 Cirebon City so that PKN learning outcomes can be improved. This study uses the Classroom Action Research (CAR) methodology. The researcher chose the Kemmis and McTaggart model of classroom action research because the research model is simple, easy to implement, and considered according to the researcher's ability. Improvement of learning outcomes in norms and rules material, namely from the aspect and aspect of student comfort in groups, as well as friends to discuss. According to the results of the research on pre-cycle learning activities, the percentage of student learning outcomes is only 40%, or 10 students with a minimum criterion that is not good. After improvements were made in the first cycle, it increased to 56%, or 14 students with good criteria. Even in the improvement of learning that had been carried out in the second cycle, it increased to reach 80%, or 20 students with good criteria.